2019
DOI: 10.1186/s12944-019-1107-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiling of suction blister fluid: comparison of lipids in interstitial fluid and plasma

Abstract: Background Recent technical advances in the extraction of dermal interstitial fluid (ISF) have stimulated interest in using this rather unexploited biofluid as an alternative to blood for detection and prediction of disease. However, knowledge about the presence of useful biomarkers for health monitoring in ISF is still limited. In this study, we characterized the lipidome of human suction blister fluid (SBF) as a surrogate for pure ISF and compared it to that of plasma. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 43 publications
(36 reference statements)
0
33
0
Order By: Relevance
“…The cohort included 13 females and 5 males with a mean age of 50.3 years (min/max 29.0/64.3 years). The same set of samples has previously been used to analyze lipidomic profiles in SBF and plasma (4). Details of the cohort (4) and procedures for the extraction of plasma and SBF have been previously described (15).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort included 13 females and 5 males with a mean age of 50.3 years (min/max 29.0/64.3 years). The same set of samples has previously been used to analyze lipidomic profiles in SBF and plasma (4). Details of the cohort (4) and procedures for the extraction of plasma and SBF have been previously described (15).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Two areas for the use of biomarkers in ISF have been proposed: I) as an alternative to blood to monitor systemic responses (4); and II) for the analysis of molecules that reflect the local environment at the site of sampling, which cannot be quantified in the systemic circulation (5). We recently showed that ISF derived from suction blister fluid (SBF) contains many lipids in similar proportions as in plasma and that ISF could be used interchangeably with plasma to monitor risk prediction biomarkers for cardiovascular disease, such as long-chain polyunsaturated fatty acids (4).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of oleic acid, homovanillyl alcohol, and hydroxytyrosol on CM were assessed using viability assays performed 48 h post treatment of two BRAF mutated melanoma cell lines (A375 and MNT1). The concentrations tested were selected based on the literature available about the effects of these compounds on different types of cancer, as well as on the reported concentrations of oleic acid in plasma [ 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 ]. The treatment with oleic acid and homovanillyl alcohol did not affect the viability of either melanoma cell line in a statistically significant manner ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…MNT1 cells seem to be more resistant to the effect of this compound, although there is a tendency to a reduction in viability after treatment. The concentrations tested in this study were selected based on the available literature on the effect of these compounds in other types of cancer and also on the available data about plasma concentrations of oleic acid in a healthy population [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation